Enhancing Children's Resilience and Subjective Well-Being through Mother-Led Counseling: A Systematic Literature Review - Syafri, Fatrida Anugrah; Danim, Sudarwan; Dharmayana, I Wayan (KONSELOR, 2025)
This Systematic Literature Review (SLR) examines the impact of mother-led counseling on children's resilience and subjective well-being in family settings. The review was conducted using PRISMA guidelines with the Watase Uake: Research Collaboration Tools, focusing on studies published between 2020 and 2025. A total of 468 Scopus articles were initially identified, and 21 studies met the inclusion criteria for in-depth analysis. This study employs is to investigate three primary objectives: (1) the influence of mother-led counseling on children's subjective well-being and resilience development; (2) the differential effectiveness of mother-led counseling approaches based on gender; and (3) the interplay of lifestyle factors, including sleep, screen time, and physical activity, with mother-led counseling to improve children's overall well-being. Mother-led counseling, defined as counseling led by mothers to provide emotional support and coping strategies, was found to significantly enhance children's emotional resilience. The analysis highlighted gender differences, with girls benefiting more from emotional support and self-compassion strategies, while boys required additional strategies for resilience development. Additionally, lifestyle factors such as physical activity, sleep, and screen time regulation were found to interact with counseling outcomes, although the strength of evidence varied across studies. This review distinguishes mother-led counseling from broader parental interventions, emphasizing the unique role of mothers in fostering children's emotional growth. It provides a gender-sensitive framework for effective family-based counseling and offers insights for designing targeted intervention programs and policies to improve children's resilience and well-being.